2016
DOI: 10.1016/j.cmet.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue Exhibits a Glucose-Responsive Thermogenic Biorhythm in Humans

Abstract: High abundance of brown adipose tissue (BAT) is linked to lower glycaemia in humans, leading to the belief that BAT may protect against diabetes. The relationship between BAT glucose utilization and systemic glucose homeostasis has not been defined. In this paper we have characterized glycaemic excursions and BAT thermogenic responses in human brown adipocytes, BAT explants, and healthy adults through supraclavicular temperature profiling, revealing their circadian coupling in vivo and in vitro, orchestrated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 27 publications
(27 reference statements)
11
107
1
2
Order By: Relevance
“…Changes in thermogenesis are known to affect metabolic responses in animals and humans 19, 46, 47 . Therefore, we next examined glucose tolerance in Ldlr −/− and Apoe −/− mice fed a cholesterol-enriched diet housed at 22°C and 30°C ambient temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in thermogenesis are known to affect metabolic responses in animals and humans 19, 46, 47 . Therefore, we next examined glucose tolerance in Ldlr −/− and Apoe −/− mice fed a cholesterol-enriched diet housed at 22°C and 30°C ambient temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…2G). Since reduction in Pdx1 expression in pancreatic β-cells has been linked with an increased rate of apoptotic cell death [32, 33], possibly explaining the small islets, we then tested whether AAV-ΔFosB islets displayed a dysfunction in glucose-stimulated insulin secretion (GSIS). Surprisingly, despite smaller islet size and reduced Pdx-1 expression, the GSIS test performed on isolated AAV-ΔFosB pancreatic islets showed a dose-dependent increase in both basal insulin level and glucose-stimulated insulin secretion compared to control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the literature strongly supports the inverse relationship between SNS activation and glucose handling, an emerging body of work suggests that SNS innervation of brown fat (BAT) exerts a contrastingly positive effect on glucose handling and energy expenditure [15,31]. Recent studies have shown that BAT control of glucose utilization is orchestrated by SNS-sensitive uncoupling protein 1 (UCP1) and glucose transporter 4 (GLUT4) [32] and this activation is at least in part linked to the activity of hypothalamic AgRP neurons [33]. …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Considering the putative role of BAT in the control of insulin action, combined with the effect of ambient temperature on BAT activity, we hypothesized that the global increase in temperature contributes to the current type 2 diabetes epidemic. Recently, a positive association was found between outdoor temperature and glycated hemoglobin (HbA1c), 17 indicating that systemic glucose homeostasis is influenced by environmental temperature. However, the importance of this association, especially in relation to the increasing diabetes burden, has never been studied on the population level.…”
Section: Significance Of This Studymentioning
confidence: 99%